Aplikasi Pengajuan Proposal Bantuan Pada Dinas Kelautan Dan Perikanan Kabupaten Sumba Timur Berbasis Android - Marlon Pura Tanya; Arini Aha Pekuwali; Murry Albert Agstin Lobo (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
The East Sumba Regency Maritime and Fisheries Service (DKP) is responsible for developing the fisheries sector. However, the process of submitting aid proposals still uses less efficient methods. To overcome this problem, researchers developed an Android-based application for submitting aid proposals online. This application allows aid applicants to upload proposal files electronically quickly and accurately. The use of this application is expected to reduce the costs and risks of physical travel and save time in the proposal collection process. This application development method uses the waterfall method, through the stages of planning, analysis, design, implementation and testing. Testing shows that this application functions well and has high feasibility based on the System Usability Scale (SUS). In this way, this application can speed up and simplify the process of submitting aid proposals at the East Sumba DKP.